A Lattice Model of the Development of Reading Comprehension. (11th October 2016) - Connor, Carol McDonald
Abstract: In this article, I present a developmental model of how children learn to comprehend what they read, which builds on current models of reading comprehension and integrates findings from instructional research and evidence‐based models of development in early and middle childhood. The lattice model holds that children's developing reading comprehension is a function of the interacting, reciprocal, and bootstrapping effects of developing text‐specific, linguistic, and social‐cognitive processes, which interact with instruction as Child Characteristic × Instruction (C × I) interaction effects. The processes develop over time and in the context of classroom, home, peer, community, and other influences to affect children's development of proficient reading comprehension. First, I describe models of reading comprehension; then, I review the basic processes in the model, the role of instruction, and C × I interactions in the context of the lattice model. Finally, I discuss implications for instruction and research.